Corona crisis: Liquidity takes priority - Michael Hüther; Michael Grömling; Martin Beznoska; Markus Demary (Institut der deutschen Wirtschaft (IW), 2020)
The Corona crisis has clearly become an economic challenge for Europe. The spread of the virus represents both a negative supply shock and a negative demand shock across the economy at large. Securing the liquidity of companies is of top priority. Employment and household income can be stabilised through short-time allowances.
Keywords: 330